Association Study Between DRD2, DRD3 Genetic Polymorphisms and Adverse Reactions in Chinese Patients on Amisulpride Treatment - Qu, Kankan; He, Yanan; Zhang, Zhongdong; Cao, Yeli; Qin, Qiyun; Zhou, Zhenhe; Zhen, Lili (Pharmacopsychiatry, 2024)
Objective To determine if the cardiac function and “endocrinium” of Chinese patients are associated with dopamine D2 (DRD2) (rs6276) and DRD3 (rs6280, rs963468) genetic polymorphisms when treated with amisulpride.Methods This study enrolled 148 patients with schizophrenia who took amisulpride orally for 8 weeks. DRD2 (rs6276) and DRD3 (rs6280, rs963468) genetic polymorphisms were detected with TaqMan-MGB allelic discrimination.Results Analysis by multivariate covariance analysis (MANCOVA) showed that after adjusting for age, gender, and the baseline level, the increase in the level of aspartate aminotransferase (AST) and creatine kinase (CK) in the rs6276 AG group was higher than that in the AA and GG groups. Similarly, the changed estradiol (E2) level in rs6276 GG and rs963468 GG groups was higher than that in the other two groups. Adjusting for covariates, the increased triglyceride (TG) level in rs6276 GG and rs963468 GG groups was the highest among their different genotype groups. The increase in the level of “AST” in the rs6280 TT group was higher than that in the CC and CT groups upon adjusting for covariates. Similarly, MANCOVA showed that the increase in the level of “CK” in the rs6280 CT group was higher than that in the CC and CT groups. Besides, the increased level of “PRL” in the rs6280 CC group and rs963468 GG group was higher than that in their other two genotypes groups.ConclusionDRD2 (rs6276) and DRD3 (rs6280, rs963468) polymorphisms can affect amisulpride tolerability since they are associated with the observed adverse reactions, including cardiac dysfunction and endocrine disorders in Chinese patients with schizophrenia.
Keywords: DRD2; DRD3; genetic polymorphisms; amisulpride; adverse reactions